Assessment of Batch and Fixed Bed Processes for Competitive Removal of Direct Dyes by a Grade III Compost Adsorbent: Relative Efficacy Factor - Al-Zawahreh, Khaled; Barral, María Teresa; Paradelo, Remigio (Water, air, and soil pollution, 2024)
There is an increasing attention for using compost in remediation of heavy metals, textile dyes and emerging contaminants. In this work, the competitive uptake of two weakly interacting dyes, Direct Blue 71 and Direct Blue 151, by compost is examined. The optimum uptake of both dyes in single and bi-solute systems is achieved at pH 3.0, 240 min equilibrium time, 25 °C, and a relatively high compost dose 3.0 g L −1 . Using Langmuir model, the maximum individual uptake of dyes by compost is 117.5 and 102.5 mg g −1 for DB151 and DB71, respectively. These values, estimated from their single-solute solution, were used to assess their overall competition under batch and fixed bed conditions. Under batch conditions, both dyes are removed from bi-solute solutions with higher competition for DB151 against DB71. The estimated competitive factors were 0.70 and 0.80 for DB71 and DB151, respectively. With a combined uptake capacity of 162 mg g −1 for both dyes, the performance of compost is promising. The fixed bed uptake of dyes indicated 80% utilization of compost capacity for single-solute solutions, at bed-depth 20 cm, flow rate 10 mL min −1 and inlet concentration 150 mg L −1 . However, dyes adsorption under dynamic conditions is making only 40 and 60% of the maximum capacity of DB71 and DB151, respectively. The incomplete utilization is attributed to the fact that dynamic conditions are not as favorable to reach equilibrium as the batch process. The relative efficacy factor r exp was then used to select the optimum treatment process. From single and bi-solute solutions, dyes are effectively removed by fixed bed adsorption as r exp < 1.0, however, batch process is recommended to remove DB71 in the presence of DB151 as r exp > 1.0.